The Impact of Electronic Money, Inflation, Interest Rates, Foreign Exchange Reserves, and the Amount of Money Supplied in Foreign Currencies in Indonesia - Rusdi Hidayat Nugroho; Faris Ihsan; Faris Shafrullah; Leni Indrawati; Solahuddin bin Ismail; Asral; Kusnan; Dani Hadibrata (Migration Letters, 2023)
Money serves as a means of trade and a unit of account for the purchase and exchange of goods and services, as well as a form of wealth storage. Talking about money is inextricably linked to the amount of money in circulation, which includes the amount of money in society, banks, institutions, and even the government. The amount of money in circulation is affected by a number of variables that cause it to fluctuate every year. This study tries to identify a number of variables that affect the money supply, such as the short- and long-term effects of e-money, inflation, interest rates, and foreign exchange reserves and exchange rates. This study makes use of secondary data that was collected over a 15-year period, from 2008 to 2022, from the Central Bank and the Central Statistics Agency. Multiple Linear Regression Analysis is the method of analysis that is employed, and it uses the Stata program’s computer tool to display the interaction between independent and dependent variables. The findings of this study demonstrate that factors such as interest rates, foreign exchange reserves, short- and long-term e-money variables, and exchange rates all significantly affect the amount of money in circulation in Indonesia. The amount of money in circulation in Indonesia is mostly unaffected by the inflation variable.